The Role of Technology in Higher Education : Exploring Current Trends and Challenges in Life Sciences Teaching and Learning - Thaware Vivek Hanmantrao (International Journal of Scientific Research in Science and Technology, 2024)
One of the key elements of India's 2030 strategy for sustainable development is high-quality education. It seeks to guarantee all students receive a high-quality, inclusive education. Digital technology has become a vital instrument in accomplishing this objective. Digital technologies aim to increase productivity and efficiency while reducing or eliminating waste and pollution. Both students' and teachers' lives have been made easier by technological advancements in education. Students today employ a variety of software and tools to develop presentations and projects with the aid of the internet, as opposed to writing by hand. This survey studywas conducted during September 2023 to December 2023 that looks into how life sciences are now taught and learned in higher education, with an emphasis on how technology is being used in the classroom. In order to obtain understanding of the application of technologically improved teaching techniques, difficulties encountered, and new trends in life sciences education, the study looks at the views of both faculty members and students also this survey research explores the contemporary patterns influencing the use of technology in life sciences education.
Keywords: Higher Education; Technology; Life-Sciences; Pedagogy